Analisis Multiakad dalam Gadai Sawah Pendekatan Emik - sholihah, nurlailiyah aidatus (ITB AAS INDONESIA Surakarta, 2024)
This article aims to analyze the practice of hybridcontract in rice field pawn contracts based on an emic perspective. The research method used is qualitative and the data source is taken from interviews with the parties involved in pawning. The type of data in this research is qualitative data. Data collection techniques were carried out through observation and interviews with the parties involved in pawning rice fields. The data analysis technique is carried out by explaining the implementation of pawning rice fields and then analyzing it using an emic approach. Based on research conducted, it shows that hybridcontracts in rice field pawning take place when the pawned rice field is then managed by the rice field owner, then the harvest obtained is divided between the rahin and murtahin based on the agreement at the beginning of the contract. This practice contains two contracts, namely a pawn contract and a rent or maro contract. This aims to protect the rights of the pawnbroker as the holder of the margin. The implementation of gadai maro provides benefits for rahin and murtahin, which is fairer for both parties according to the pawn actor.